Bladder cancer biomarker analysis and drugtarget prediction based on pyroptosis-related genes - Ping Li; Xuexi Yang; Qin Liu; Hanchao Zhang; Zhumei Luo (Discover Oncology)
Abstract Background Bladder cancer (BC) is a common and lethal condition that presents a considerable risk to public health. Studies have demonstrated that inflammation is pivotal in the onset and advancement of BC. Pyroptosis is a type of programmed cell death distinguished by inflammatory reactions associated with innate immunity. Inhibiting inflammatory cytokine production and modulating pyroptosis-related pathways may provide a potential treatment approach for BC. We predicted and validated the Pyroptosis-related genes and potential biomarkers associated with BC, ultimately predicting therapeutic drugs based on the hub gene targets. Methods The gene expression profiles for BC were acquired from the Gene Expression Omnibus (GEO) database. Bioinformatics analysis identified gene expression differences associated with pyroptosis in BC. The differently regulated pyroptosis-related genes were validated, and enrichment studies of specific biological processes and associated signaling pathways in BC were performed. Immune infiltration analysis and single-cell analysis were conducted to clarify the immune infiltration characteristics in BC. Therapeutic agents were forecasted based on critical gene targets. Results In BC, 27 differentially expressed pyroptosis-related genes were discovered, with CASP8, NLRP3, CASP3, IL18, TP53, GSDME, IL1A, PYCARD, CYCS, and CASP9 recognized as key genes. Enrichment analysis revealed that the occurrence of pyroptosis was primarily associated with inflammation, activation of immune responses, and apoptosis. Additionally, data validation demonstrated that CASP8, NLRP3, CASP3, IL18, TP53, CYCS, and CASP9 were involved in the regulation of pyroptosis. The results of immune infiltration and single-cell analyses further validated that B-cells-memory, T-cells_CD8, T-cells_follicular-helper, Macrophages-M1, Dendritic_cells_activated, and Mast_cells_resting play significant roles in the immune processes of BC. The drug targeting predictions for pivotal genes identified Triethyl phosphate, Regorafenib, Ponatinib, Lenvatinib, Nintedanib, and Quercetin as potential key drugs or compounds for the treatment of BC. Conclusion This study elucidated the relationship between the development of BC and mechanisms of cellular senescence, apoptosis, and immunity. It clarified the roles of 27 genes associated with cellular senescence in BC and predicted that Triethyl phosphate, Regorafenib, Ponatinib, Lenvatinib, Nintedanib, and Quercetin may be key drugs or compounds for the treatment of BC.